After Anna [compact disc, unabridged] - Scottoline, Lisa (Macmillan Audio, 2018)
Noah Alderman, widower and single father, has remarried a wonderful woman. But their lives are turned upside down when her daughter moves in with them. Unbeknownst to everyone, Anna is not simply a selfish beauty, but a dangerously disturbed sociopath. When she turns up dead, Noah is at the top of the suspect list. Noah begins his own investigation in order to clear his name and save his family, and what he discovers is darker than he could have ever imagined.